Kesenjangan Pendidikan dan Determinannya di Indonesia - Dwi Ari Suryawan. S; Teguh Sugiyarto (Politeknik Statistika STIS, 2022)
Human capital investment is an effort to improve the quality of human capital, such as through education, training, medical care, and many else. In line with that, education achievement is a prominent indicator of human capital. This condition must be acknowledged and obtain adequate attention because education inequality also affects economic development indirectly, through its effect on economic efficiency. The purposes of this research is to classify inequality of education and what determines it. The methodology used in this research are descriptive and inferential analyzes. The Descriptive analyzes were used to see description or general pictures of education in Indonesia, also to classify inequality of education, using cluster of hierarchy. The inferential analyzes used in this research is binary logistic regression, the purpose is to inferences variables which significantly affect inequality of education in Indonesia. The results show that provinces in Indonesia classified into two categories based on inequality of education, the low education level and good education level, 17 provinces included into low education level and 17 provinces included to good education level, in percentage, it is 50% to 50% . It is also showed which variables significantly affect inequality of education statistically, like education expenditure and poverty in province’s level.